Transient hyperphosphatasemia – where do we stand? - Kutílek, Štěpán; Bayer, Milan (The Turkish Journal of Pediatrics, 1999)
Transient hyperphosphatasemia of infancy and early childhood (THI) is characterized by transiently increased serum activity of alkaline phosphatase (S-ALP), predominantly its bone or liver isoform, in children under five years of age. There are no signs of metabolic bone disease or hepatopathy corresponding with the increased S-ALP, nor is there a disease common to all children with THI. To date, THI has been reported in more than 400 children. Viral etiology of THI has been proposed; transiently increased bone turnover and impaired clearance of ALP from the serum were originally considered as its causes. The pathogenesis is most probably multifactorial. THI is a benign disorder, as prospective follow-up of children with a history of TH revealed normal growth and normal bone density. Children with TH should be spared from excessive diagnostic procedures.